Dampak Pandemi Covid 19 Terhadap Tingkat Pengangguran di Kelurahan Tanjung Pura - Salsabila Rahmawan, Fadia (Rifa'Institute, 2021)
The Corona virus pandemic, also known as Covid-19, shook peopleall across the world in 2020, having a significant impact on people'slives and causing terror. The purpose of this paper is to look into theeffect of Covid-19 on unemployment in Tanjung Pura community.Qualitative approaches and library research were employed asresearch methodologies. Secondary data in the form of scientificpublications with literature reviews or literature reviews wasemployed in this investigation. The findings of the study suggestthat the Covid-19 epidemic has had a significant impact on theunemployment rate. The PSBB or Lockdown was implemented as akind of government anticipation to ensure that there would be nofurther contagion, but it has had an impact on economic growth, oneof which being a rise in the unemployment rate.